FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN WAJIB PAJAK (STUDI PADA WAJIB PAJAK ORANG PRIBADI KPP PRATAMA TAMPAN PEKANBARU) - Lastri Lastri; Vince Ratnawati; Novita Indrawati (PEKBIS, 2018)
This study aims to analyze the effect of system quality, information quality, securityand confidentiality on the taxpayer's personal satisfaction of the users of e-filling fortax reporting, and also want to investigate the moderating role of service quality. Thepopulation in this study are all individual taxpayers who use e-filling system as taxreporting in Tax Office Pratama Tampan Pekanbaru. The sampling technique usedaccidental sampling method which resulted sample of 100 respondents. We usedmultiple linear regression and moderated regression analysis for hypothesis testing.The results showed that security and confidentiality did not affect taxpayersatisfaction, while system quality, information quality have significant effect ontaxpayer satisfaction. We also found that the service quality moderates the effect ofquality system, information quality, security and confidentiality on taxpayersatisfaction.